Phagosomal TLR signaling upon Borrelia burgdorferi infection - Cervantes, Jorge L.; Hawley, Kelly L.; Benjamin, Sarah J.; Weinerman, Bennett; Luu, Stephanie M.; Salazar, Juan C. (Frontiers in Cellular and Infection Microbiology, 2014)
Internalization of live Borrelia burgdorferi followed by their degradation within phagosomal compartments, allows for the release not only of lipoproteins but of other microbial products, such as nucleic acids, needed to elicit a full and broad inflammatory response in monocytes/macrophages. Toll-like receptors (TLRs) are key players in the recognition of ligands from whole viable organisms (i.e. vita-PAMPs). Although the immune system has evolved mechanisms to prevent stimulation by self-nucleic acids, nucleic acid-sensing TLRs can trigger innate immune activation resulting in induction of autoimmunity. Endosomal TLR variations could not only lead to an increased susceptibility to Lyme disease, but also determine the severity of its clinical symptoms. With a deeper understanding of the TLR pathways, we will be able to create better treatments and more thoroughly understand the mechanism of disease in patients.